Friend or foe? (Economist, 2003)
The rise of Linux is dividing the computer industry into winners and losers. Larry Ellison, the boss of Oracle, the world's second-largest software firm, likes to make bold claims. Last week he was at it again, attacking his old foe, Microsoft, the world's biggest software company. Microsoft, he declared, risked being "wiped off the face of the earth" by Linux, the free, open-source operating system developed by Linus Torvalds, a Finnish programmer, and a team of enthusiasts. The rise of Linux is changing the dynamics of the computer business. Some of the industry's titans benefit from its advance, while others lose. Linux has yet to have much impact in the highest echelons of business computing: telecommunication-billing systems, airline-reservation systems, and so on. The main loser (so far) as Linux advances is Sun Microsystems, one of the largest server vendors. Its Solaris software is generally deemed to be the most capable flavour of Unix, the family of powerful operating systems used in servers. This has forced Sun to embrace the technology that threatens its existence. Last year, Sun launched its first Linux-based server. As well as offering cheap boxes running Linux alongside its more powerful Solaris-based ones, Sun will include its server software with both Linux and Solaris, to make its Linux boxes more attractive and to allow users to "trade up" to Solaris. Linux has also boosted IBM's mainframe business, since a single mainframe can be set up to behave like dozens of small Linux servers.